2018
DOI: 10.1098/rsos.172428
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silicon on growth mechanism of micro-arc oxidation coating on cast Al–Si alloy

Abstract: Micro-arc oxidation (MAO) is a plasma-assisted electrochemistry method to prepare protective ceramic coatings on aluminium alloys. Alloy elements of the Al-alloy substrate, such as Si, Cu, Mg and Li, have effects on the microstructure and composition of the MAO coatings. Usually, silicon distributes in the cast Al–Si alloy substrate as small laths and they cover approximately 10% of the substrate surface. Therefore, their effects on the growth process and microstructure of the MAO coatings are worthy of notice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The ultrahigh temperature on the local surface of the workpiece promotes violent oxidation of both the β-Si and α-Al phase, and leads to a ceramic layer in-situ growing on the surface of Al-Si alloys. Besides, as a simple and eco-friendly technique, the MAO can fabricate coatings with high performance, e.g., high hardness, good anticorrosion and wear resistance [10,11]. In this regard, the MAO technique is more suitable for the surface strengthening of Al-Si alloys [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The ultrahigh temperature on the local surface of the workpiece promotes violent oxidation of both the β-Si and α-Al phase, and leads to a ceramic layer in-situ growing on the surface of Al-Si alloys. Besides, as a simple and eco-friendly technique, the MAO can fabricate coatings with high performance, e.g., high hardness, good anticorrosion and wear resistance [10,11]. In this regard, the MAO technique is more suitable for the surface strengthening of Al-Si alloys [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Yu et al treated a eutectic cast Al-Si alloy using a phosphate-based electrolyte [27]. The PEO processes were performed at a low current density, between 4 and 6 A•dm −2 , and resulted in low-thickness PEO coatings (8-10 µm), in which no α-Al 2 O 3 phase was detected.…”
Section: Peo Coatings Developed On Cast Al-si Alloys Using Phosphate-...mentioning
confidence: 99%
“…Furthermore, Wang & Nie suggested that during passivation, the film grows inward, whereas when Al or Si oxides are formed, there would be some expansion in the volume of the formed layer. According to Yu et al [27], the thickness of the layer created during the initial passivation stage (in the order of nanometers) is significantly lower than the roughness of the substrate (in the order of microns). Thus, these authors believed that the boundary effect prevented the initiation of discharges and proposed a new growth mechanism consisting of three steps: passivation, stable oxidation, and final oxidation stages.…”
Section: Peo Coatings Developed On Cast Al-si Alloys Using Phosphate-...mentioning
confidence: 99%
See 1 more Smart Citation
“…SEM observation of the MAO coating surface shows a characteristic pancake structure whose morphology evolves with the processing conditions [83,[86][87][88]. The cross-sections of the coatings reveal a structure for the thin layers for which there is little distinction between the brittle layer and the dense layer [84,86,89].…”
Section: Composition Of Coatingsmentioning
confidence: 99%